Assessment of the environmental risk of some heavy metals in the groundwater of Jableh plain (Latakia University Journal -Basic Sciences Series, 2019)
Presence of heavy metals in ground water used for drinking purpose is considered to be hazardous to human health. The aim of this study is to estimate the concentrations of some heavy metals (Cadmium, Lead, Copper, Zinc, Iron) in the groundwater of Jableh plain - Lattakia.Groundwater samples were collected from eleven different sources from the Jableh plain area, and concentrations of these heavy metals were determined using atomic absorption spectrophotometer. The concentration of cadmium in the water samples ranges from 0.056 to 1.022 µg/l, while lead concentrations were between 1.51 and 13.58 μg/l. The concentration of elements (Cd, Pb, Cu, Zn, Fe) were within the allowed limits according to Syrian standards for drinking water, Lead concentration in one location1 was upper than allowed limits, Contamination Index (CI), Average Daily Dose (ADD) and Hazard Quotient (HQ) for each metal were calculated. The mean of Contamination Index (CI) value was 0.186 and the higher value was 0.481, which is classified as (not contaminated). The values of Hazard Index (HI) were